CRITERIA AND METHODS FOR ASSESSING THE INFORMATION SECURITY COMPETENCE OF FUTURE TEACHERS (Scientific journal of the Fergana State University, 2026)
This article analyzes the criteria and methods for assessing the information security competence of future teachers. In the context of digital transformation, mastering knowledge, skills, and abilities in information security is becoming increasingly important. Therefore, the training of teachers requires scientifically grounded approaches to competence assessment. The study examines theoretical sources, modern pedagogical technologies, and diagnostic tools, and proposes effective assessment criteria. The results contribute to enhancing the professional preparation of future teachers, strengthening the culture of information security, and creating a safe educational environment.